Historical linguistics 2015: selected papers from the 22nd International Conference on Historical Linguistics, Naples, 27-31 July 2015 - Cennamo, Michela; Fabrizio, Claudia; Parlato, Renato (Amsterdam studies in the theory and history of linguistic science, 2019)
Introduction / Michela Cennamo and Claudia Fabrizio -- Part I. Phonology: 1. Old Irish consonant quality re-examined / Hans Henrich Hock -- 2. The use of the past to explain the past: Roman grammarians and the collapse of quantity / Marco Mancini -- 3. Pertinacity in loanwords: Same underlying systems, different outputs / Aditi Lahiri and Holly Kennard -- Part II. Morphology: 4. Ablaut in Armenian nasal declension / Giancarlo Schirru -- 5. Gender and declension mismatches in West Nordic / Ivar Berg -- 6. The development of gender and countability effects in German ung- and English ing-nominals / Martina Werner and Gianina Iordachioaia -- 7. Some new evidence on the rise of Italian -ata nouns / Claudia Fabrizio -- 8. Diachrony and morphological equilibrium: The case of the southern New Indo-Aryan verb / Paolo Milizia -- 9. Anti-relevant, contra-iconic but system-adequate: On unexpected inflectional changes / Livio Gaeta -- Part III. Morphosyntax: 10. Impersonal passives and the suffix -r in the Indo-European languages / Francesco Rovai -- 11. The Old English verbal prefixes for- and ge-: Their effects on the transitivity of morphological causative pairs / Esaúl Ruiz Narbona -- Part IV. Syntax: 12. Enclitic -(m)a 'but' / -(y)a 'and' in Hittite: Losing extraordinary syntactic behavior / Andrei V. Sideltsev -- 13. State representation and dynamic processes in Homeric Greek: The case of the aorist in -hn / Domenica Romagno -- 14. The actualization of language change: Perfect and middle in Indo-European languages / Romano Lazzeroni -- 15. Early Indo-European dialects and innovations of aspect systems / Jadranka Gvozdanovic -- 16. Perfecting the notion of Sprachbund: Perfects and resultatives in the 'Stratified Convergence Zones' of Europe / Bridget Drinka -- 17. Parameters in the development of Romance perfective auxiliary selection / Adam Ledgeway -- 18. Adverbs and the left periphery of non-finite clauses in Old Spanish / Teresa María Rodríguez Ramalle and Cristina Matute -- Part V. Diachronic typology: 19. The sources of antipassive constructions: A cross-linguistic survey / Andrea Sansò -- 20. A diachronic account of converbal constructions in Old Rajasthani / Krzysztof Stronski, Joanna Tokaj and Saartje Verbeke -- Part VI. Semantics and pragmatics: 21. The locative alternation with spray/load verbs in Old English / Katarzyna Sówka-Pietraszewska -- 22. Penetration of French-origin lexis in Middle English occupational domains / Richard Ingham, Louise Sylvester and Imogen Marcus -- 23. Meaning change from superlatives to definite descriptions: A semantic approach / Jun Chen and Dawei Jin -- 24. Towards diachronic word classes universals / Matthias Gerner -- 25. Grammaticalizing the face (as well as the hands) in a first generation sign language: The case of Zinacantec Family Homesign / John B. Haviland -- Part VII. Language contact, variation and diffusion: 26. Linguistic divergence under contact / Nicholas Evans -- 27. Roots and branches of variation across dialects of English / Sali A. Tagliamonte -- 28. Waves in computer simulations of linguistic diffusion / Luzius Thöny.
Includes bibliographical references and index
Keywords: Konferenzschrift -- 27.07.2015-31.07.2015 -- Naples; Historische Sprachwissenschaft